Evaluation of protein content and labeling compliance in protein bars marketed as dietary supplements (Research, Society and Development, 2025)
The growing public interest in healthy eating habits and physical activity has driven the consumption of dietary supplements, among which protein bars stand out for their convenience and high protein content. However, the reliability of nutritional labeling information has been increasingly questioned in recent studies. This study aimed to evaluate the protein content and nutritional labeling compliance of protein bars marketed as dietary supplements in Brazil, according to the tolerance limits established by RDC No. 243/2018, IN No. 28/2018, and RDC No. 429/2020 of the Brazilian Health Regulatory Agency (Anvisa). Twenty different brands were randomly purchased in the city of Marília, São Paulo. The protein content was determined using the Kjeldahl method, according to the Instituto Adolfo Lutz (2008), and compared with the values declared on product labels. All samples presented protein levels above the minimum required (8.4 g per serving); however, 35% of them showed deviations greater than ±20%, indicating non-compliance with current labeling regulations. The discrepancies observed represented overestimations of the declared values, possibly influenced by the presence of non-protein nitrogen compounds. These findings demonstrate that, although the products meet the minimum requirements for dietary supplements, labeling inconsistencies persist, highlighting the need for stricter manufacturing control and continuous regulatory oversight. Future studies should address the nutritional composition and inter-batch variability to improve the understanding of product quality and labeling accuracy.